Modernização agrícola e as transformações sócioespaciais de Caldas Novas-GO - Ottobeli, Delmar (2005)
The object of this study is to present the results of research on the transformations in the agrarian space of Caldas Novas, Goiás, beginning in 1970, as well as the socio-economic implications and the elements of alteration of this space. Use was made of bibliographic research covering the themes related to the development of farming and cattle ranching in the Mid-West region and in the State of Goiás since 1970, drawing from books, magazines, newspaper articles, periodicals and information available on the Internet. The field research showed changes in the agricultural environment of Caldas Novas with an assimilation of new production techniques evidenced in properties undergoing an adaptation in land usage, going from rudimentary open range cattle ranching to seasonal soybean and corn farming regimes. At the same time the county undergoes a process of incorporation and usage of agricultural equipment, insecticides and fertilizers because the local soils require chemical corrections and adaptations for the practice of modern agriculture. Many still do not make use of modern technology for financial reasons or for not knowing of the advantages of increased productivity. Finally, it can be affirmed that there is a concentration of crops in one region of the county (flat lands) where there is a greater modernization in agriculture and even in cattle ranching. It is in the hilly lands that the more backward and rudimentary ranching prevails. The growth in agriculture and ranching complements the touristic aspect of the county, which developed after the founding of Brasília in the 1960 s, and whose hidrothermal potential is greatly exploited as the main source of the county s economy.